Detection of Leishmania infantum in naturally infected Lutzomyia longipalpis (Diptera: Psychodidae: Phlebotominae) and Canis familiaris in Misiones, Argentina: The first report of a PCR-RFLP and sequencing-based confirmation assay - Acardi, Soraya Alejandra (2010)
In this study, a genotypification of Leishmania was performed using polimerase chain reaction-restriction fragment length polymorfism (PCR-RFLP) and sequencing techniques to identify species of Leishmania parasites in phlebotomine sand flies and dogs naturally infected. Between January-February of 2009, CDC light traps were used to collect insect samples from 13 capture sites in the municipality of Posadas, which is located in the province of Misiones of Argentina. Sand flies identified as Lutzomyia longipalpis were grouped into 28 separate pools for molecular biological analysis. Canine samples were taken from lymph node aspirates of two symptomatic stray animals that had been positively diagnosed with canine visceral leishmaniasis. One vector pool of 10 sand flies (1 out of the 28 pools tested) and both of the canine samples tested positively for Leishmania infantum by PCR and RFLP analysis. PCR products were confirmed by sequencing and showed a maximum identity with L. infantum. Given that infection was detected in one out of the 28 pools and that at least one infected insect was infected, it was possible to infer an infection rate at least of 0.47% for Lu. longipalpis among the analyzed samples. These results contribute to incriminate Lu. longipalpis as the vector of L. infantum in the municipality of Posadas, where cases of the disease in humans and dogs have been reported since 2005.